Protocol of prevention and treatment of pressure ulcers - Francisco José García Sánchez; Francisco López Salazar; Elena González Urraca; Pilar Romero Valverde; Mª Carmen Martínez García; José María Flores López-Ibarra (Fundación para el Desarrollo de la Enfermería, 2008)
The care of wounds, specially the ones produced by the pressure, has been and it keeps on being a challenge for all the health professionals, especially for nurses, which still today cannot be considered as totally solved.Nobody may deny the magnitude of the problem that chronic wounds nowadays supposes in this country. There are thousands of people who demand nursing assistance everyday to take care of the problems derived from chronic wounds.Starting off of these premises it has been considered to approach a standardized and protocolized performance of the professionals regarding the care of wounds, to unify criteria that favour the continuity of cares between the different levels and that all the nursing actions were suppported by a common norm, being possible to register, evaluate and research them.The unification of criteria and performance guidelines in the prevention and treatment of the wounds is one of the main objectives that we marked ourselves due to the increasing number of prophylactic and therapeutic options available, that makes it necessary to prepare nurses for making them being able to choose the most suitable tool to reach the objectives marked in the care of wounds.